Micropaleontological Analysis of Planktonic and Benthic Foraminifera from the Claystone Member of the Bayah Formation (Tebm) and the Limestone Member of the Cijengkol Formation (Tojl), Jatake Area, Lebak Regency, Banten Province - Salsabiila Fadhilah Ahmad; Dwi Vina Febrim; Harnani Harnani (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2025)
Micropaleontological analysis of planktonic and benthic foraminifera from three rock samples—muddy micrite, allochemic sandstone, and wackestone—was carried out to determine the relative age and depositional environment of the Claystone Member of the Bayah Formation (Tebm) and the Limestone Member of the Cijengkol Formation (Tojl) in the Jatake area, Lebak Regency, Banten Province, Indonesia. A total of 43 foraminiferal specimens were identified, including 28 planktonic and 15 benthic individuals. These were used for biostratigraphic and paleoenvironmental interpretation. The results show that the Claystone Member Tebm (RL19) dates to the Middle Eocene, mainly within planktonic foraminiferal biozones P14–P15, which falls under a wider P14–P17 range. In contrast, the Limestone Member Tojl is younger, with sample RL85 assigned to the Late Oligocene (N1–N3) and sample RL23 corresponding to the Late Oligocene to earliest Miocene interval (N3–N4). Benthic foraminiferal groups from all samples suggest deposition in outer neritic to upper bathyal environments. The estimated paleobathymetric ranges are about 390–1100 ft for RL19, 350 - 1630 ft for RL85, and 390 - 1230 ft for RL23. Even though the ages differ, the similarity in depositional environments hints at comparable marine bathymetric conditions in the study area. The differences in age suggest that the Bayah Formation and the Cijengkol Formation represent different depositional phases instead of a continuous stratigraphic sequence. This finding offers important insights into the stratigraphic framework and depositional evolution of the Bayah Dome region.